2011
DOI: 10.1016/j.jsps.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the pharmaceutical quality of marketed enteric coated pantoprazole sodium sesquihydrate products

Abstract: Pantoprazole sodium sesquihydrate (PSS) is a proton pump inhibitor, used in acid-related disorders, like peptic ulcer and gastroesophageal reflux. Increasing the number of pantoprazole containing products in the market, raises questions of its efficacy and generic substitution. The pharmaceutical quality of 6 generic PSS enteric coated tablets in 2 local markets was assessed relative to the innovator product (pantozol®). Uniformity of dosage unit, disintegration and in vitro drug release were determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…The leaching of PVP from the membrane leads to formation of pores, and thus the release of drug takes place. In a previous study with sorbitol as pore-former, the pore size in the CA coating membrane after dissolution was reported as 1 -15 µ, which is significantly higher than that of formulation developed in this study 4 . The lower pore-size occurred with PVP in current formulation due to the fact that PVP polymer due to its longer chain length intrigued into the cellulose polymer coating.…”
Section: Scanning Electron Microscopycontrasting
confidence: 55%
See 2 more Smart Citations
“…The leaching of PVP from the membrane leads to formation of pores, and thus the release of drug takes place. In a previous study with sorbitol as pore-former, the pore size in the CA coating membrane after dissolution was reported as 1 -15 µ, which is significantly higher than that of formulation developed in this study 4 . The lower pore-size occurred with PVP in current formulation due to the fact that PVP polymer due to its longer chain length intrigued into the cellulose polymer coating.…”
Section: Scanning Electron Microscopycontrasting
confidence: 55%
“…Dissolution parameters include, USP apparatus II, 500 mL of pH 6.8 phosphate buffer, paddle speed 50 RPM, medium temperature 37 ± 0.5°C. 10 mL of samples were removed from the dissolution apparatus (Disso 2000, Lab India, Thane, India) at regular time intervals up to 24 h (1,2,4,8,12,16,20, and 24 h) and replaced with the same volume of fresh dissolution medium. Samples were filtered through 0.45 µm membrane filter and analyzed by UV-Visible spectrophotometer (Cary C50, Varian Inc., Palo Alto, CA, USA) at 223 nm to determine the cumulative percent drug release.…”
Section: In-vitro Release Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The growing number of proton pump inhibitors containing marketed pharmaceutical products increases the questions about the enteric coating efficiency of generic substitution. In our previous work [18]. The pharmaceutical quality control of 6 generic pantoprazole (PPIs) enteric coated tablets in 2 local markets was assessed relative to the innovator product.…”
Section: Lansoprazole (Lnz) Is a Benzimida-zole Derivative;mentioning
confidence: 99%
“…As per<711>USP for delayed release dosage forms, not more than 10% of the drug should be released in acidic media after 120 min. Hence, it was proved that the prepared microspheres were gastroresistant [37,38]. It was concluded that the developed microspheres would prevent drug release in the acidic medium of the stomach so that intestinal absorption of the drug would be improved, leading to increased bioavailability.…”
Section: In Vitro Drug Releasementioning
confidence: 99%